IMPLEMENTASI UNDANG-UNDANG NOMOR 20 TAHUN 2023 BERDASARKAN GRAND DESIGN REFORMASI BIROKRASI 2010-2025 - rawinarno, tjahyo; Alynudin, Suhud; Shafira , Najwa; Widiarto, Agus; Setyoko, Haryo (LPPM STIA Banten, 2024)
ABSTRACT Bureaucratic Reform in Indonesia almost ten years after announced. The one of aim is assurance Civil Servant give the service for public efficiently. Accrossingly, still found that some issues need to be improve. So, through this research can be one of implementation solution regard Law Number 20 Year 2023. Used qualitative method based on Bureaucratic Reform Grand Design 2010-2025. The result is this approach able to make the goal sukses. Key Words: Bureaucratic Reform; Law; Implementation